Efficacy and Safety of Kilohertz Frequency Alternating Current with Non-Invasive Electrodes for Treatment of Neuropathic Pain After Spinal Cord Injury: A Randomized, Single-Blind, Sham-Controlled Study - Shuai N; Zhu Y; Xiao Y; Yu B (Journal of Pain Research, 2025)
Niannian Shuai,1,* Yuyao Zhu,2,* Yao Xiao,3,* Bin Yu4 1Department of Anesthesiology, Ningbo University Affiliated People’s Hospital, Zhejiang, People’s Republic of China; 2Department of Anesthesiology, Shanghai Tongji Hospital, Shanghai, People’s Republic of China; 3Department of Rehabilitation, Shanghai Tongji Hospital, Shanghai, People’s Republic of China; 4Department of Pain Rehabilitation, Yangzhi Rehabilitation Hospital, Affiliated with Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin Yu, Department of Pain Rehabilitation, Yangzhi Rehabilitation Hospital, Affiliated with Tongji University, 2209 Guangxing Road, Songjiang District, Shanghai, 201613, People’s Republic of China, Tel +86 139 1810 8880, Email yubin@tongji.edu.cnObjective: To evaluate the effectiveness and safety of noninvasive kilohertz frequency alternating current (KHFAC) therapy for neuropathic pain in patients following spinal cord injury.Methods: In this randomized, single-blind, sham-controlled trial conducted from June 1, 2023, to January 31, 2024, 50 patients suffering from neuropathic pain post-spinal cord injury were assigned to receive either KHFAC or sham stimulation for 7 days, complemented by twice-daily oral administration of 75 mg pregabalin. Outcomes were assessed using the Visual Analog Scale (VAS), Pittsburgh Sleep Quality Index (PSQI), and Brief Pain Inventory (BPI) at baseline, at the end of treatment, and 30 days post-treatment. The primary outcome was the effective rate at the end of treatment, defined as a decrease in VAS score of 30% or more.Results: At the end of the 7-day treatment period, the experimental group demonstrated a significantly higher response rate, with 60% of participants achieving a 30% or greater reduction in VAS scores compared to 28% in the control group (X²=5.195, P< 0.05). During this initial period, KHFAC effectively decreased pain intensity, reduced the frequency of paroxysmal pain, and lessened the need for additional analgesics. It also improved sleep quality and overall quality of life relative to sham stimulation. However, at the 30-day follow-up, no statistically significant differences were observed between the groups.Conclusion: KHFAC is effective and safe for short-term neuropathic pain relief and quality of life enhancement in spinal cord injury patients, without an increase in adverse events versus sham stimulation. However, while reductions in analgesic use suggest potential lasting benefits, the long-term effectiveness remains uncertain. Further studies are required to assess the persistence of these effects.Trial Registration: Chinese Clinical Trial Registry, ChiCTR2300068114. Keywords: neuropathic pain, kilohertz electrical stimulation, patch electrode, spinal cord injury, visual analog scale